Oxytetracycline in intensive aquaculture: water quality during and after its administration, environmental fate, toxicity and bacterial resistance - Joana F. Leal; Eduarda B.H. Santos; Valdemar I. Esteves (Reviews in Aquaculture, 2019)
Oxytetracycline ( OTC ) is one of the most used antibiotics in aquaculture. This raises concerns due to its effects in human and animal health, the environmental contamination and the consequences arising therefrom. This review focuses on the OTC application in intensive aquaculture. It compiles and complements the dispersed information, presenting a comprehensive study about the OTC effects, from its administration to farmed fish, until its release into the surrounding aquatic systems. Several topics about OTC are presented and discussed: physical–chemical properties, interaction with ions, application to farmed fish, effects in water quality and possible treatments, biological activity and toxicity of OTC by‐products, environmental fate. Based on the information gathered, one concludes that OTC establishes strong complexes with Ca 2+ and Mg 2+ , which may have implications on its biological activity. OTC acts as inhibitor of protein synthesis and is poorly metabolized or unmetabolized by fish. Its common recommended daily dose is about 75 mg kg −1 but depends on the administration conditions and on target fish species. Regarding OTC removal from water within a semiclosed aquaculture's water circuit, ozonation and photodegradation are not completely efficient methods as none of them promotes total mineralization. However, photodegradation can be applied as a complementary method prior to ozonation, allowing to reduce costs. OTC by‐products do not appear to retain its biological activity, but toxicity studies mimicking environmental conditions were not found. In open circuits (cages), water column where OTC is administered not suffer a specific treatment and the antibiotic is easily spread by the surrounding environments, affecting their inhabitants. OTC is released in the aquatic system in freely dissolved form and/or associated with organic or inorganic compounds, being subjected to natural photolysis, hydrolysis and/or biodegradation.